2014
DOI: 10.3122/jabfm.2014.04.130276
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Preschool Children: A Review of the Diagnostic Challenges

Abstract: Family physicians face many challenges when diagnosing asthma in preschool children. These diagnostic challenges are compounded by variations in the natural history of early stage asthma, which are not fully understood, since early childhood wheezing and asthma are heterogeneous disorders with many phenotypic and variable expressions. Since no standard definition for the type, severity, or frequency of symptoms exist for this age group, clear evidence-based recommendations are lacking. Without adequate guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 63 publications
0
35
0
1
Order By: Relevance
“…The physician-diagnosed phenotypes of atopic diseases were evaluated by the same pediatric pulmonologist at the outpatient clinics. Asthma was diagnosed as ever having asthma, with the occurrence of recurrent wheeze in the last 12 months, or current use of asthma medication, based on the guidelines of the Global Initiative for Asthma 28 . Allergic rhinitis was diagnosed as having symptoms such as sneezing, nasal congestion, itching, and rhinorrhea in the last 12 months 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The physician-diagnosed phenotypes of atopic diseases were evaluated by the same pediatric pulmonologist at the outpatient clinics. Asthma was diagnosed as ever having asthma, with the occurrence of recurrent wheeze in the last 12 months, or current use of asthma medication, based on the guidelines of the Global Initiative for Asthma 28 . Allergic rhinitis was diagnosed as having symptoms such as sneezing, nasal congestion, itching, and rhinorrhea in the last 12 months 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are no specific treatments for asthma and long-term standard treatment may reduce the recurrence of asthma, but evidence has also suggested that early intervention is essential for the patients with asthma (5–8). However, the diagnosis of asthma in children is difficult and easily misdiagnosed, which may result in under treatment of asthmatics or overtreatment of transient wheezes and lead to lung function impairment (9). Therefore, a correct and timely diagnosis of asthma in children is the first step towards effective management and treatment of asthma, which may reduce the potential harm due to misdiagnosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is the most common chronic inflammatory disease of childhood, characterized by periodic obstruction of the airways and respiratory symptoms such as wheezing, cough and breathlessness [1]. It affects one child in 7 in some societies and approximately 300 million individuals worldwide.…”
Section: Introductionmentioning
confidence: 99%